Formulation development of an enzyme-antibiotic combination for treatment of biofilm infections - Agnar Þór Hilmarsson 1993- (2018)
Biofilms are formed by microbes, such as bacteria, as a defense mechanism from external substances like antibiotics, environmental hazards, and in response to nutritional deficiencies. Bacteria accumulate inside the biofilm which creates optimal living situation for the bacteria to grow. This feature makes the struggle against infections caused by the microbes more difficult to handle. The antibiotics erythromycin and moxifloxacin are used to treat infection caused by biofilm forming microbes but those antibiotics cannot treat the biofilm itself. Some enzymes have shown potential to be effective against biofilms formed by microbes and of special interest is the serine protease trypsin that is derived from the Atlantic cod. Although numerous antibiotics are available to treat bacteria, bacteria can develop resistance to them, making them useless after a certain amount of time. That shows the need for constant improvement in new antibiotics or treatments to keep bacterial infections at bay or to eliminate them. The aim of this project was to develop a formulation effective against both the bacteria and the biofilm formed by the bacteria, to treat chronic infections. Combination of trypsins and erythromycin or moxifloxacin were used in a water/glycerol based formulation. Erythromycin did not affect the trypsin activity in the formulation over six weeks at 25°C or over 10 days at 40°C. On the other hand, erythromycin was not stable over seven weeks at 40°C and the results from the stability test at 25°C indicated stability over seven weeks but more accurate quantification method for erythromycin is needed. Conversely, moxifloxacin had negative effect on the trypsin activity over six weeks at 25°C and over 10 days at 40°C but the stability of moxifloxacin in the formulation was unaffected at 25°C and 40°C, over seven weeks. Results from this study lay the groundwork for further development of an enzyme-antibiotic combination formulation for the treatment of biofilm infection.